Cytotoxicity Definition, Identification, and Cytotoxic Compounds - Salih Istifli, Erman; Basri Ila, Hasan (IntechOpen, 2019)
Compensating for cytotoxicity in the multicellular organism by a certain level of cellular proliferation is the primary aim of homeostasis. In addition, the loss of cellular proliferation control (tumorigenesis) is at least as important as cytotoxicity, however, it is a contrasting trauma. With the disruption of the delicate balance between cytotoxicity and proliferation, confrontation with cancer can inevitably occur. This book presents important information pertaining to the molecular control of the mechanisms of cytotoxicity and cellular proliferation as they relate to cancer. It is designed for students and researchers studying cytotoxicity and its control.